Manajemen Sekolah Sepak Bola Klub Jaya Karsa Pada Masa Pandemi Covid-19 di Kota Palangka Raya - Cukei Cukei; Siskaevia Siskaevia (FKIP Universitas Palangka Raya, 2023)
Problems in the management of the Jaya Karsa football school club, Palangka Raya City, still need to be addressed, one of the soccer players said that in soccer at every practice or match we feel we lack technical mastery and our physical condition decreases, we get tired quickly. This research aims to identified the management of the Jaya Karsa Club football school during the covid 19 period in Palangka Raya City. This type of research is descriptive qualitative research, data collection by interview, observation and documentation study. The subjects in this study included: primary data of the Jaya Karsa Football Club school, coaches (1 person), and secondary data, namely one athlete player (1 person), data analysis techniques, namely data reduction means summarizing, display, namely the researcher breaking down the data related to the management of the Jaya Karsa Club football school, Verification is Drawing conclusions in data analysis activities that are more specific to the interpretation of the data that has been presented. The results showed that the management of the Jaya Karsa football school club in Palangka Raya City was carried out jointly by the administrators and coaches at the football school. The training program used at the research site was made by the coach of the Jaya Karsa football school club, Palangka Raya City, based on the competition calendar issued by the SSB Management in Palangka Raya City. The coach makes an exercise program to be used as a guide in carrying out the training program so that the training is more in line with the competition so that athlete achievements can be achieved.